Kualitas Pelayanan Publik Bidang Jasa Pengiriman pada PT Pos Indonesia (Persero) Kota Pematangsiantar - Lubis, Muhammad Fahri Irawan; Bi Rahman, Nur Ahmadi (ManBiz: Journal of Management and Business, 2023)
This research was conducted aiming to improve the quality of public services in the field of delivery services at PT. Pos Indonesia (Persero) Pematangsiantar City. Of course, customer satisfaction reflects their assessment of a company. Companies are challenged to build an image and can provide quality and satisfying services. Every company should know what they need to improve. This study aims to determine to what extent the quality of public services in freight forwarding services. Qualitative descriptive method was used to conduct this research. The method of collecting data is by making direct observations at the PT. Pos Indonesia Office in Pematangsiantar City. The results of this study indicate that service delivery and service quality are very influential on customer satisfaction. And they must be able to provide service innovations in order to be able to survive and compete with their competitors. Keywords: Service Quality, Customer Satisfaction, Innovation